Pergeseran Paradigma: Dari Penilaian Tradisional Menuju Penilaian Inovatif Dalam Kurikulum Bahasa Arab Modern - Riza Egy Ramadhani; Baiq Tuhfatul Unsi; M. Yunus Abu Bakar (Institut Muslim Cendekia, 2026)
Global educational transformation demands a repositioning of evaluation systems in language learning to remain relevant to the competencies required in the 21st century. This study aims to analyze the paradigm shift from rigid traditional assessments toward more adaptive innovative assessments in the modern Arabic curriculum. Using a descriptive qualitative methodology through literature review and content analysis, this research examines various curriculum documents and recent literature related to language assessment. The findings show that innovative assessments, such as digital portfolios and authentic assessments, provide a more comprehensive picture of learners’ competencies compared to conventional standardized tests, which tend to measure only theoretical cognitive aspects. The novelty of this study lies in the integration of modern educational philosophical principles with the practical needs of Arabic language proficiency in the digital era. The implications of this research emphasize the importance of reorienting the role of educators and curriculum policies to adopt more performative evaluation instruments. Overall, this shift serves as a catalyst for enhancing the quality of Arabic language learning outcomes to be more competitive and professional.